MODULE BASED ON 5E LEARNING CYCLE TO TRAIN CRITICAL THINKING IN CIRCULATORY SYSTEM CONCEPT - Rahayu, Nugraheni Ngesti; Antika, Rindi Novitri; Nizkon, Nizkon (FMIPA UNNES, 2019)
This study aimed to 1) Know the module product description based on 5E learning cycle models developed to train critical thinking skills, 2) Know the feasibility of modules based on 5E learning cycle models on the circulatory system material designed to train students critical thinking skills. This research was done by research and development according to Borg and Gall (2003) which was limited to step 7. The data analysied by descriptive qualitative and quantitative data analysis. Qualitative descriptive used to process the overall questionnaire assessment data in the form of opinions and suggestions from the material expert validators, media experts, linguists, evaluation experts, education practitioners (biology teachers) and XII science students. Quantitative descriptive analysis was used to analyze the assessment scores of the respondents regarding the feasibility of the module. Based on the results of the validation by experts, the validation of material experts got 74,96% with good qualifications, data from the presentation or media validation results got an average of 74.49% with good qualifications, language validation got an average of 79.37% with good qualifications and evaluation validation got an average of 74.76% with good qualifications. Validation by educational practitioners got an average of 86,66% with excellent qualifications and validation by students got an average of 88,46% with good qualifications. Based on the overall percentage, it could be concluded that the module was feasible to use.